1988
DOI: 10.1073/pnas.85.4.1297
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of amyloid-beta-protein mRNA expression within hippocampal neuronal subpopulations in Alzheimer disease.

Abstract: We have mapped the neuroanatomical distribution of amyloid-fi-protein mRNA within neuronal subpopulations of the hippocampal formation in the cynomolgus monkey (Macaca fascicularis), normal aged human, and patients with Alzheimer disease. Amyloid-8-protein mRNA appears to be expressed in all hippocampal neurons, but at different levels of abundance. In the central nervous system of monkey and normal aged human, image analysis shows that neurons of the dentate gyrus and cornu Ammonis fields contain a 2.5-times-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 31 publications
3
40
1
Order By: Relevance
“…Other studies have suggested differences in neuronal subpopulation expression of APP mRNA [190]. An effect of age and anatomical region is supported by a study of cynomolgus monkeys in which APP 695 and 751 were increased 2 -7 times in the thalamus in 17-year-old monkeys when compared with 3-year olds [337].…”
Section: Human Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…Other studies have suggested differences in neuronal subpopulation expression of APP mRNA [190]. An effect of age and anatomical region is supported by a study of cynomolgus monkeys in which APP 695 and 751 were increased 2 -7 times in the thalamus in 17-year-old monkeys when compared with 3-year olds [337].…”
Section: Human Studiessupporting
confidence: 57%
“…The hydrophilic residues in Aβ contribute to the specificity of the interactions between Aβ peptides and may influence the transformation from a β pleated sheet structure to a random coil [187]. Aβ deposits are not found in rodent brain and this might relate to differences in the amino acid sequence between rodents, and other species-unknown factors independent of the primary structure might also influence fibril formation [188][189][190][191]. Amyloid structures in mammalian tissues might encourage covalent polymerization of reactive small molecules into larger molecules like melanin with cytoprotective properties.…”
Section: In Vitro Studies: Aβmentioning
confidence: 99%
“…One study has reported the presence of the mRNA for amyloid precursor protein (APP) in the dendrites ofneurons in culture (Strong et al, 1990). Studies of APP mRNA distribution in tissue sections do not suggest a dendritic localization, however (Higgins et al, 1988;Lewis et al, 1988). There is also evidence that a nonmessenger RNA termed BCl is present in dendrites (Tiedge et al, 1991a,b).…”
mentioning
confidence: 99%
“…While the mechanism by which the OA4 peptide is generated from APP is unknown, overexpression of the APP in Alzheimer's disease has been proposed as a possible mechanism of APP metabolism disturbance Higgins et al, 1988;Palmert et al, 1988;Tanzi et al, 1988;Johnson et al, 1989Johnson et al, , 1990Neve et al, 1988Neve et al, , 1990. In this way, the 150% increase in APP gene expression in trisomy 21 might be related to the formation of the abundant senile plaques found in the cerebral cortex of Down's syndrome patients (Rumble et al, 1989 (Chirgwin et al, 1979).…”
Section: Transfection Of Chimeric Cdna Constructsmentioning
confidence: 98%
“…In Alzheimer's disease, such a gene dosage effect has not been established (Podlisny et al, 1987). However, an increase in the expression of APP mRNA Higgins et al, 1988) or modifications in the differential expression of APP isoforms (Palmert et al, 1988;Johnson et al, 1989;Neve et al, 1988Neve et al, , 1990) have been reported in Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%